Short-duration hyperoxia causes genotoxicity in mouse lungs: protection by volatile anesthetic isoflurane - Kundumani-Sridharan, Venkatesh (Am J Physiol Lung Cell Mol Physiol, 2019)
High concentrations of oxygen (hyperoxia) are routinely used during anesthesia, and supplemental oxygen is also administered in connection with several other clinical conditions. Although prolonged hyperoxia is known to cause acute lung injury (ALI), whether short-duration hyperoxia causes lung toxicity remains unknown. We exposed mice to room air (RA or 21% O(2)) or 60% oxygen alone or in combination with 2% isoflurane for 2 h and determined the expression of oxidative stress marker genes, DNA damage and DNA repair genes, and expression of cell cycle regulatory proteins using quantitative PCR and Western analyses. Furthermore, we determined cellular apoptosis using TUNEL assay and assessed the DNA damage product 8-hydroxy-2′-deoxyguanosine (8-Oxo-dG) in the urine of 60% hyperoxia-exposed mice. Our study demonstrates that short-duration hyperoxia causes mitochondrial and nuclear DNA damage and that isoflurane abrogates this DNA damage and decreases apoptosis when used in conjunction with hyperoxia. In contrast, isoflurane mixed with RA caused significant 8-Oxo-dG accumulations in the mitochondria and nucleus. We further show that whereas NADPH oxidase is a major source of superoxide anion generated by isoflurane in normoxia, isoflurane inhibits superoxide generation in hyperoxia. Additionally, isoflurane also protected the mouse lungs against ALI (95% O(2) for 36-h exposure). Our study established that short-duration hyperoxia causes genotoxicity in the lungs, which is abrogated when hyperoxia is used in conjunction with isoflurane, but isoflurane alone causes genotoxicity in the lung when delivered with ambient air.